Precise location of three novel linear epitopes using the generated monoclonal antibodies against the Knob domain of FAdV-4 surface structural protein, fiber1 - Chai, Yongxiao; Jin, Qianyue; Zhu, Rongfang; Guo, Zhenhua; Lu, Qingxia; Chai, Shujun; Xing, Yunrui; Han, Lu; Xing, Guangxu (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundFowl adenovirus serotype 4 (FAdV-4) is the main pathogen of hepatitis-hydropericardium syndrome (HHS), which brings huge economic losses to the poultry industry worldwide. Fiber-1 protein plays an important role in viral infection and pathogenesis by binding directly to cellular receptors of FAdV-4. In particular, the knob domain of fiber-1 protein has been reported to induce the production of neutralizing antibodies and arouse protection against the lethal challenge of chickens with FAdV-4.MethodsThe fiber-1 knob (F1K) protein was expressed in a prokaryotic expression system and purified using Ni-NTA affinity chromatography. Monoclonal antibodies (mAbs) against FAdV-4 were generated by immunizing BALB/c mice with the purified F1K protein and screened using a series of immunoassays. Potential B cell epitopes on the knob domain of fiber-1 protein were mapped using enzyme-linked immunosorbent assay (ELISA) and dot-blot. Precious location and crucial amino acids of the identified epitopes were determined using peptide array scanning, truncations and alanine-scanning mutagenesis. The epitopes were analyzed and visualized on the knob trimer of FAdV-4 fiber-1 protein using the PyMOL software.ResultsWater-soluble recombinant fiber-1 knob (F1K) protein was obtained with the assistance of chaperone. Four monoclonal antibodies (5C10, 6F8, 8D8, and 8E8) against FAdV-4 were generated and characterized using indirect ELISA, Western blot, dot-blot, and immunological fluorescence assay (IFA). The mAbs were demonstrated to be from different hybridoma cell lines based on the sequences of the variable regions. Meanwhile, three distinct novel linear B-cell epitopes (319SDVGYLGLPPH329, 328PHTRDNWYV336, and 407VTTGPIPFSYQ417) on the knob domain of fiber-1 protein were identified and the key amino acid residues in the epitopes were determined. Structural analysis showed that the two adjacent epitopes 319SDVGYLGLPPH329 and 328PHTRDNWYV336 were exposed on the surface of the fiber-1 knob trimer, whereas the epitope 407VTTGPIPFSYQ417 was located inside of the spatial structure.ConclusionThis was the first identification of B-cell epitopes on the knob domain of fiber-1 protein and these findings provided a sound basis for the development of subunit vaccines, therapeutics, and diagnostic methods to control FAdV infections.